Meeting National Science Standards in an Integrative Curriculum: Classroom Examples from a Rural Middle Level Program - Bruno G. Hicks (Journal of Research in Rural Education, 1997)
The new science education standards generated by national and state organizations are challenging middle level programs across the country to alter their school's curriculum. In their most recent position statement, the New England League of Middle Schools (1995) called on middle level programs to adopt a curriculum that was integrated and not separated by single subject boundaries. Attempting to dissolve the boundaries ofthe separate subjects has pushed middle level teachers and administrators into a process of exploring feasible options for blending the science curriculum with other disciplines. To meet the challenge, many middle level programs use the integrative curriculum planning strategies outlined by James Beane (1990, 1993). Curriculum development under the best ofcircumstances is hard work, but it can be especially 'challenging for small, rural schools that perceive small size and strained economic resources as limiting factors in this endeavor (Lee & Milburn, 1994). Although Beane's (1990) curriculum planning process, in several different forms, is used by middle level programs across the country, research concerning the effectiveness ofthis curricular approach is sparse (Beane, 1993; MacIver & Epstein, 1993). This report examines the effectiveness ofan integrated curricular model operating in a rural middle level program in meeting the national life science curriculum standards as outlined by the National Research Council (NRC, 1996).